Simple User Assistance Driving Algorithm for Cost-Effective Smart Electric Wheelchair - Erturk, Esranur; Lee, Dongyoung; Kim, Soonkyum (2022 31st IEEE International Conference on Robot and Human Interactive Communication (RO-MAN), 2022)
Wheelchairs are among the most important equipment in terms of facilitating the lives of people with walking disabilities. In particular, the use of electric wheelchairs allows people with walking disabilities to move comfortably without excessively straining their bodies. However, in some cases, a person with a walking disability who uses an electric wheelchair may have difficulties in driving the wheelchair or may experience unintended collisions due to obstacles that are not within the line of sight. In order to prevent such negative events, it is necessary to develop a wheelchair with electric wheels that is produced at a minimum cost, can be easily sold to all kinds of people with disabilities, and will not be difficult to use. In addition, this equipment must include a system designed to provide wheelchair control and driving comfort with maximum efficiency for areas outside of the line of sight, which is one of the features required by all people with walking disabilities. This article explains the design of a prototype that can detect blind spots thanks to sensors and provide driving comfort while a wheelchair driver with walking disabilities uses it. In this paper, it is aimed to create a smart electric wheelchair that can be used by anyone with a walking disability while keeping the costs to a minimum.